Economic Analysis of Household Processing Sugar Nagari Bukik Batabuah Agam District - Alvindo Dermawan; Nofialdi Nofialdi; Yusmarni Yusmarni (Talenta Publisher, 2019)
This study aims to describe household economic processing brown sugar and identify the factors that affect decision sugar confection red and household consumption processing brown sugar in nagari bukik batabuah kecamatan canduang kabupaten agam. Methods used are the method survey. Populations are all households processing brown sugar traditionally in nagari bukik batabuah kecamatan canduang kabupaten agam with 528 unit households. A method of the respondents is by means simple random sampling as many as 30 households respondents. Analysis the data used was deskripsitif qualitative. The result of this research is that torrent of working hours in in the processing brown sugar greater than activities outside processing brown sugar so income derived from the sale of red is also greater of income outside activities processing brown sugar of rp.2.581.667 or 82 % household income comes from income brown sugar, their household needs processing brown sugar could not be fulfilled some of their income spent for consumption needs food without capable of savings and invest. Factors that affects decision sugar confection red in nagari bukik batabuah is the number of raw materials, sugar price red and needs of the households, while that affects household consumption processing brown sugar namely household income, the number of family members, and the number of families to that are still at school. Advice provided researchers that is as well